Pengaruh Prasarana dan Aksesibilitas terhadap Kualitas Pelayanan Transportasi Mass Rapid Transit Jakarta - Ramadhan, Fauzan Fitrah; Sudarman, Daman (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to analyze the effect of infrastructure and accessibility on the quality of service of the Jakarta Mass Rapid Transit (MRT). Infrastructure and accessibility each act as an independent variable, while service quality is the dependent variable. This research uses a quantitative method with a survey approach involving 120 respondents, namely Jakarta MRT service users. Data were collected using an online questionnaire with a Likert scale to measure infrastructure, accessibility, and service quality variables. Data analysis techniques include validity, reliability, classical assumption, and multiple linear regression tests processed using SPSS V 20. The results showed that infrastructure has a significant positive effect on service quality with a coefficient value of 0.437. Accessibility also has a significant positive effect on service quality with a coefficient value of 0.377. Simultaneous test results show that infrastructure and accessibility together have a significant effect on service quality with a calculated F value of 45,612 and a significance level of 0.000 (p < 0.05). The contribution of the two variables to service quality is indicated by the coefficient of determination (R²) of 0.648, which indicates that 64.8% of variations in service quality can be explained by infrastructure and accessibility. This study provides recommendations to PT MRT Jakarta to continue to improve service quality.